Electrochemical Synthesis on Nanoparticle Chains to Couple Semiconducting Rods: Coulomb Blockade Modulation Using Photoexcitation. (14th August 2014) - Pu, Long; Abbas, Abdullah Saud; Maheshwari, Vivek
<x xml:space="preserve">Abstract</x> Hybrid nanostructures are made by coupling a room temperature coulomb blockade device with photoexcitable nano‐rods. Direct electrochemical synthesis on nanoparticle chain arrays leads to the formation of semiconducting rods that are in direct contact with the nanoparticles and also spatial confined by them. This direct interfacing leads to mutual intermodulation between the two systems. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>